The effects of ethnic origin and gender dimorphism on auricular morphometry: a cross-sectional study - Karacan, Keziban; Erdogan, Mehtap; Celik, Halit (Journal of the Pakistan Medical Association, 2026)
Objective: To analyse the auricular in terms of ethnicity and gender by morphometric measurements. Method: The cross-sectional study was conducted at Sakarya University, Sakarya, Turkiye, from January 2022 and January 2023, and comprised students of Turkish and African descent. Isolated ear photographs of the subject were analysed using the ruler software, and anatomical measurements, such as ear length, length of the ear above and below the tragus, ear width, concha length, and the distance between otobasion superior and otobasion inferior, were noted. Data was analysed using SPSS 26 software. Results: Of the 68 subjects, 34(50%) were Turkish with mean age 20.37 ± 3.1 years, while 34(50%) were of Africans with mean age 20.19 ± 3.2 years. Both the groups had an equal number of male and female participants. Gender-based differences among Turkish participants were significant, with Turkish males exhibiting higher values than females (p<0.05). The gender-based differences were not significant among African subjects (p>0.05). Significant differences were found between the groups in terms of tragus-to-ear length, tragus-to-lobe length, tragus height, and the distance between otobasion superior and otobasion inferior (p<0.05). Conclusion: Auricular anthropometry exhibited significant variations based on gender and ethnicity. Key Words: Anthropometry, Auricula, Ear measurements, Gender differences, Morphometry.